Development Towards Maturity: A Literature Review on Desired Outcomes in Youth Ministry, Part 1 - Kock, Jos de (Journal of youth and theology, 2024)
This article is the first of two centring around the theme of desired outcomes of youth ministry practices, which are often embedded in a certain conception of spiritual maturity. The review study which forms the basis for these two articles aims to construct a theoretical framework on desired outcomes in youth ministry on the basis of a systematic literature review of scholarly works in peer-reviewed journals regarding the subject published from 1996 up to 2021. The wide range of outcomes as observed in the literature is classified by describing three areas of youth ministry goals: the areas of spiritual development, personal development and social development. Current, first, article accounts for the particularities of the research design of the review study and presents the outcomes found in the literature within the particular area of spiritual development. The review study as a whole and this particular article contribute to a broader academic area of interest in how to envision or define spiritual maturity, particularly Christian maturity, and what this means for formational practices such as youth ministry.